A Watershed Based Approach for ravine reclamation and control - Singh, Y. P.; Verma, S. K.; Singh, Akhilesh; Verma, G. P. (Indian Farming, 2017)
The cultivable land - a basic resource for agriculture is shrinking fast due to not only diversion to nonagricultural use but also due to different types of chemical and physical degradations. Water erosion accounts for the biggest degradation and ravine formation is the most severe form of water-erosion. Since ravines are formed by erosive action of run-off water, rainwater management on watershed basis is the appropriate approach for ravine reclamation and control.